2008
DOI: 10.2105/ajph.2006.098467
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of an Internet-Based Partner Notification System for Sexually Transmitted Infection Exposure Among Men Who Have Sex With Men

Abstract: US men who have sex with men (n=1848) completed an online questionnaire about their willingness to use Internet-based partner notification. Eighty-one percent reported that it would be important to them to receive a partner notification e-mail if they had been exposed to a sexually transmitted infection. Seventy percent reported that if infected, they would use a public health specialist to inform partners of possible exposure through Internet notification. There was broad acceptance of Internet partner notifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
26
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 15 publications
1
26
1
Order By: Relevance
“…On the basis of currently available evidence, we do not believe that clinicians should routinely use PDPT in MSM. Our results related to inSPOT contrast with prior evaluations documenting that many people visit the inSPOT site, 3 that many MSM find internet partner notification sites acceptable, 11,12 and that approximately 6% of MSM with access to inSPOT send e-cards to someone. 4 We found that virtually no MSM wanted to use inSPOT, even though using e-mail to notify partners was common.…”
Section: Discussioncontrasting
confidence: 99%
“…On the basis of currently available evidence, we do not believe that clinicians should routinely use PDPT in MSM. Our results related to inSPOT contrast with prior evaluations documenting that many people visit the inSPOT site, 3 that many MSM find internet partner notification sites acceptable, 11,12 and that approximately 6% of MSM with access to inSPOT send e-cards to someone. 4 We found that virtually no MSM wanted to use inSPOT, even though using e-mail to notify partners was common.…”
Section: Discussioncontrasting
confidence: 99%
“…For example, the finding that Internet users were no more or less likely to be generative versus non-generative seeds suggests that while the Internet may be useful for HIV prevention and education activities [38][39][40][41] as well as for public health functions such as partner notification, 42,43 it may not be the a Comparisons were made between generative and non-generative seeds using Chi-square global tests of independence and Fisher's exact tests where cell sizes were small. Median group differences were calculated using Wilcoxon rank-sum test statistics.…”
Section: Discussionmentioning
confidence: 99%
“…Surveys of STI clinic patients in the US and Australia, as well as of MSM internet users in the US, have found high levels of acceptability for web-based notification systems (24)(25)(26). In Europe and Australia, provider-managed internet notification has also been found useful in supporting PN during routine clinical practice (27)(28)(29).…”
Section: Introductionmentioning
confidence: 99%